Targeted therapy for lung cancer: reviewing the cost and its effect on treatment decisions. (December 2014) - Lim, Charles; Sergi, Melissa; Leighl, Natasha B
SUMMARY : Novel targeted therapies that improve outcome in advanced lung cancer should be adopted. However, given the high costs of targeted therapies and companion molecular testing, the affordability and cost–effectiveness of novel agents are of growing relevance in policy decisions. Incremental cost–effectiveness ratios in excess of US$200, 000 per quality-adjusted life year have been described in published literature evaluating currently approved agents. Differing willingness to pay thresholds in different countries determine which therapies will be funded in a given healthcare system. Cost-containment strategies to address costs of molecular testing and drug acquisition need to be implemented. Drug manufacturers, healthcare payers and oncologists have a shared responsibility to ensure that novel therapies are affordable and accessible to patients in need.